2014
DOI: 10.1016/j.urolonc.2013.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Multi-institutional analysis of sequential intravesical gemcitabine and mitomycin C chemotherapy for non–muscle invasive bladder cancer

Abstract: Objective Apart from cystectomy, few treatment options exist for the management of bacillus Calmette-Guerin refractory non–muscle invasive bladder cancer (NMIBC). We report a multi-institutional experience with sequential intravesical combination chemotherapy using gemcitabine and mitomycin C (MMC) for NMIBC in the treatment of high-risk patients. Methods We performed a retrospective review of patients who received 6 weekly treatments with sequential intravesical gemcitabine (1 g) and MMC (40 mg) chemotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 20 publications
0
67
0
2
Order By: Relevance
“…[31] Similarly, a multi-institutional retrospective study of high-risk NMIBC patients treated with sequential intravesical gemcitabine followed by MMC demonstrated recurrence-free survival rates of 50% at 12 months. [32] Given the encouraging outcomes, a phase I trial is underway to evaluate the safety of various combinations of chemotherapeutic agents, such as cabazitaxel, gemcitabine, and cisplatin when given intravesically in patients with BCG-unresponsive NMIBC.…”
Section: Bcg-unresponsivementioning
confidence: 99%
“…[31] Similarly, a multi-institutional retrospective study of high-risk NMIBC patients treated with sequential intravesical gemcitabine followed by MMC demonstrated recurrence-free survival rates of 50% at 12 months. [32] Given the encouraging outcomes, a phase I trial is underway to evaluate the safety of various combinations of chemotherapeutic agents, such as cabazitaxel, gemcitabine, and cisplatin when given intravesically in patients with BCG-unresponsive NMIBC.…”
Section: Bcg-unresponsivementioning
confidence: 99%
“…(33) A multi-institutional analysis for sequential intravesical Gemcitabine with Mitomycin C found that patients with high-grade NMIBC or BCG refractory disease had a 2 year recurrence free survival of nearly 40%. (34) These studies lend further evidence that salvage protocols utilizing Gemcitabine in this setting show promise.…”
Section: Maintenance Bcgmentioning
confidence: 73%
“…87,88 Sequential gemcitabine-mitomycin C in 47 patients with highrisk disease, primarily after BCG failure, resulted in a complete response in 68% of patients with 1year and 2year diseasefree survival of 48% and 38%, respectively. 89 Alternatively, sequenced g emcitabine-docetaxel in 45 patients with highrisk disease yielded a complete response rate of 66%, as well as 1year and 2year recurrencefree survival of 54% and 34%, respectively. 90 Reassuringly, although the cystec tomy rate for both regimens was around 20%, metastasis was rarely reported.…”
Section: Consensus Statementsmentioning
confidence: 99%